Auricular reconstruction with polyethylene implants or silicone prosthesis: A single institution experience. Issue 12 (December 2018) - Al Kadah, Basel; Naumann, Andreas; Schneider, Mathias; Schick, Bernhard; Linxweiler, Maximilian; Papaspyrou, Giorgos
Abstract: Auricular reconstruction is usually necessary in patients with congenital malformations, after traumatic ear amputations or in cases of neoplastic ear disease. Thirty-nine patients who underwent an auricular reconstruction with either silicon prosthesis (21 patients) or porous polyethylene (18 patients) between 2002 and 2013 were retrospectively analyzed at a tertiary academic institution. A total of 25 male und 14 female patients were included in the study. In all, 43 implants were installed in 39 patients. An implant failure was not observed in any of the examined groups. An operative revision was necessary in 5 patients in the silicon prosthesis group (N = 21) and in 4 patients in the porous polyethylene group (N = 18). The most common side effect in the porous polyethylene group was the formation of retroauricular adhesions in 11.1 % by postoperative scaring, while in the silicone prosthesis group 71.4 % of the patients presented with skin reactions around the titanium implants. Our study shows that both techniques are valuable and should be offered to patients in cases of auricular reconstruction due to the low rate of severe complications and the good functional results of both techniques.